Entrepreneurial Orientation in the Context of Small Business Development - Renata LISOWSKA (Communications of International Proceedings, 2021)
The dynamics and complexity of the environment force small businesses to build a sustainable competitive advantage by exploring new opportunities. The concept of entrepreneurial orientation reflects the extent to which the development goals of these enterprises are driven by the identification and exploitation of market opportunities. Therefore, the aim of the paper is to discuss the importance of entrepreneurial orientation in the context of small business development and to present the results of the research on the level of entrepreneurial orientation of Polish small enterprises. The survey was conducted using the CATI technique among owners/co-owners of micro and small enterprises operating in Poland in October and November 2019. The size of the analysed sample was 400. The following statistical tests were used to assess the level of entrepreneurial orientation in the surveyed companies: Cronbach’s alpha, Bartlett's test of sphericity, the Mann-Whitney and Kruskal-Wallis tests, the Kaiser-Meyer-Olkin test, and Spearman's correlation coefficient. The research results show the impact of entrepreneurial orientation on enterprise development, i.e., the higher the level of entrepreneurial orientation, the higher the level of development orientation. Additionally, the following conclusions have been formulated: (i) there is a relationship between the level of entrepreneurial orientation and the age of the enterprise, (ii) there is a relationship between the level of entrepreneurial orientation and the stage of enterprise development, (iii) there is no relationship between the level of entrepreneurial orientation and the size of the enterprise.
Keywords: Entrepreneurial Orientation; Enterprise Development; Development Priorities; Small Business.